Composition of Essential Oil of Leaves Stems and Roots by Different Extraction Methods of Thymus kotschyanus Boiss. & Hohen var. pseuderiophorus Rech. f.p.p. Grown Wild in Iran - Aberomand Azar, Parviz; Aghaei Meibodi, Zahra; Saber-Tehrani, Mohammad; Larijani, Kambiz (Asian Journal of Chemistry, 2011)
The essential oils of leaves, stems and roots of Thymus kotschyanus Boiss. and Hohen var. pseuderiophorus Rech. f. p.p. (Lamiaceae) that obtained by hydro distillation (HD), solvent free microwave extraction (SFME), microwave assisted extraction (MAE) with hexane and mixture of water and hexane, solid phase micro extraction (SPME) were analyzed by means of GC and GC/MS. Identification of components was done by comparison of the relative retention indices and mass spectra with authentic reference. In all of the above methods, carvacrol was the major compound in the oils of different organs. The identified compounds in the oil of leaves, stems and roots represent (98.4, 99.6, 97.7, 99.6 and 98.4 %), (99.3, 92.5, 99.1, 99.1 and 99.8 %) and (98.3, 99.9, 98.4, 97.1 and 100 %), respectively of the essential oils.